Risk Factors for Complications after Reduction Mammoplasty: A Meta-Analysis - Zhang, Min-Xia; Chen, Chun-Ye; Fang, Qing-Qing; Xu, Ji-Hua; Wang, Xiao-Feng; Shi, Bang-Hui; Wu, Li-Hong; Tan, Wei-Qiang (PloS one, 2016)
Reduction mammoplasty (RM) is a proven method of treating macromastia, but the risk factors for postoperative complications have not been clearly identified. Through this meta-analysis, the authors aimed to identify the risk factors of RM complications. An extensive search of the literature describing complications after RM was performed using the PubMed Central, Embase, and Cochrane databases. The following risk factors were extracted: age, body mass index (BMI), tissue resection weight per breast (TRW), smoking and radiation therapy. Odds ratios (OR) were pooled with 95% confidence intervals (CI) to evaluate the relationship between these risk factors and complications after RM. A total of 16 unique studies including 10 593 patients were included in the final analysis. It showed that there was a significant difference in complications in BMI ≥30 kg/m2 (OR 0.73; 95% CI: 0.61-0.89, p = 0.001) and smoking (OR 1.56; 95% CI: 0.98-2.49, p = 0.06). Infection in those with BMI ≥30 kg/m2 showed a significant difference (OR 0.68; 95% CI: 0.52-0.89, p = 0.004), as well as wound dehiscence in smokers (OR 2.73; 95% CI: 1.60-4.67, p = 0.0002) and infection in irradiated breasts (OR 20.38; 95% CI: 3.42-121.35, p = 0.0009). However, there was no significant difference in age ≥50 years (OR 0.96; 95% CI: 0.71-1.29, p = 0.78), combined TRW ≥1000 g (OR 1.04; 95% CI: 0.43-2.50, p = 0.93). BMI ≥30 kg/m2 and smoking increase the risk of complications. Persons who are obese or irradiated are more likely to develop infections, and smokers experienced a higher incidence of wound dehiscence than did nonsmokers. However, patients aged ≥50 years and TRW ≥1000 g are not associated with complications from RM.